1988
DOI: 10.1037/h0090565
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of attention deficits in children.

Abstract: A critical analysis of the view that a general attention deficit can be identified and objectively measured in children is presented. Research regarding the specific nature of attentional difficulties in hyperactive children and the measurement of attention and attention deficits is selectively reviewed. School psychologists are cautioned against premature use of the attention deficit disorder (ADD) label and measurement strategies for the following reasons: (a) the experimental, clinical, and educational lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…The effect of this, however, is that any combination of symptoms of inattention and/or irnpulsivenesg and/or hyperactivity can result in an APHD diagnosis. As Ostrom and Jenson (1988) pointed out, "While the narrative description of ADHD in DSM-In-R highlights attentional problems, it wopld be theoretically possible to make the diagnosis without considering any of the attention items" (p. 263), Table 1 summarizes the diagnostic, erite?ria found in DSM-111 and DSM-III-R. As predicted, Meworn et al (1989) identified a group of nonreferred students meeti~g ADHD criteria who displayed hyperactive and impulsive but not necessarily inattentive behaviors. Based on this finding, the authors ooncluded that ADHD criteria allow identification of a more heterogeneous group than A D D m ariteria.…”
Section: Diagnostic Nomenclaturementioning
confidence: 99%
“…The effect of this, however, is that any combination of symptoms of inattention and/or irnpulsivenesg and/or hyperactivity can result in an APHD diagnosis. As Ostrom and Jenson (1988) pointed out, "While the narrative description of ADHD in DSM-In-R highlights attentional problems, it wopld be theoretically possible to make the diagnosis without considering any of the attention items" (p. 263), Table 1 summarizes the diagnostic, erite?ria found in DSM-111 and DSM-III-R. As predicted, Meworn et al (1989) identified a group of nonreferred students meeti~g ADHD criteria who displayed hyperactive and impulsive but not necessarily inattentive behaviors. Based on this finding, the authors ooncluded that ADHD criteria allow identification of a more heterogeneous group than A D D m ariteria.…”
Section: Diagnostic Nomenclaturementioning
confidence: 99%